Acute toxicity and quality of life in dose-escalated proton reirradiation for locally recurrent rectal cancer: The prospective ReRad II trial - C.G Truelsen; H.S Rønde; J.F Kallehauge; J.E Szpejewska; R Bahij; L.V Diness; S.K Skriver; L.Ø Poulsen; B.M Havelund; B.G Pedersen; L.H Iversen; K.G Spindler; et al. (Clinical and Translational Radiation Oncology, 2025)
Background and purpose: Locally recurrent rectal cancer (LRRC) in pre-irradiated patients remains a clinical challenge. Intensity-Modulated Proton Therapy (IMPT) enables dose escalation with potential for improved tumour control without compromising dose to organs at risk (OAR). However, prospective data on toxicity and patient-reported outcomes (PROs) with quality of life (QoL) are limited. Materials and Methods: This planned interim analysis from the prospective phase II ReRad II trial (NCT04695782) reports acute toxicity and PROs in the first 25 patients treated with dose-escalated IMPT for LRRC. Patients received either 55 Gy (relative biological effectiveness (RBE)) in 44 fractions (neoadjuvant) or 57.5–65 Gy (RBE) in 46–52 fractions (definitive). Acute toxicity was graded using NCI-CTCAE. PROs were assessed using EORTC QLQ-C30 and −CR29 questionnaires at pretreatment, during treatment, and at 3-month follow-up. A linear mixed model evaluated longitudinal PRO trajectories. Results: Among 25 patients, 49 gross tumour volumes resulted in 29 clinical target volumes (median: 84.2 cm3). Median Dmean to bladder, bowel bag, and bowel loops were 7.5, 1.8, and 11.5 Gy(RBE); corresponding D0.03cc were 58.1, 59.9, and 59.3 Gy(RBE). Grade ≥3 acute toxicity (ileus) occurred in 2 patients with pre-existing ileus episodes. Urinary retention was associated with bladder D0.03cc(Gy). PROs showed stable global health scores over time, with improvements in emotional and cognitive function. Conclusion: Interim results support the feasibility of dose-escalated IMPT reirradiation for LRRC, with manageable acute toxicity and preserved QoL. Continuance of the trial will inform long-term outcomes and guide future treatment strategies for LRRC management.